012 Improving the transition process for young people with life-limiting conditions. (1st October 2013) - Sivell, Stephanie; Lidstone, Victoria; Taubert, Mark; Thompson, Catherine; Nelson, Annmarie
Abstract : Research Aims: To identify the training needs of adult Specialist Palliative Care (SPC) teams to care for young adults and inform the development of an education package for adult SPC teams. Background: The prognosis of life-limiting conditions of childhood has improved with an increase in the number of young people accessing adult SPC services. Adult SPC teams may be inexperienced in caring for the complex needs of these young people. Methods: Delphi: An online Delphi process collated expert opinion on format, delivery and content of the educational package in three rounds. Focus Groups: Focus groups were held with young people with life-limiting conditions, staff from a local adult hospice and carers. Discussions explored the care and support needs of young people and their families, and the training needs of SPC teams. Data were analysed using thematic analysis. Results: Delphi: Consensus was reached on range suggested formats and personnel to deliver the training, and on clinical, psychosocial and practical topics. Training should be delivered as a continuous/rolling programme and not as 'a one-off'. Focus Groups: Discussions centred on: challenges of caring for young people; barriers to transition; staff education and training; facilitating transition. Conclusions: The knowledge required by adult SPC teams to meet the complex needs of young people and their families is diverse and extensive. To optimise learning, training should be delivered as a continuous/rolling programme, tailored for content and mode of delivery. A template to guide handover and a single point of contact would facilitate the transition process. Application to Hospice Practice: A series of study days has been designed using the information gathered in this research and will commence in June 2013. A template to guide handover is in development with plans to create a single point of contact to co-ordinate the transition process.